IS 2. Using computational models in tDCS research and clinical trials - Bikson, M. (Clinical neurophysiology, 2013)
Computational models of tDCS link tDCS dose (electrode montage) with the resulting brain current flow. This presentation summarizes computational tools and approaches currently available to clinicians and researchers that can be leveraged in the optimization and customization of tDCS. Even as increasingly complex and advanced modeling techniques are developed by engineering groups, clinicians and cognitive neuroscience researchers require software that is readily accessible, and does not require specialized training or significant computational resources. Approaches developed by the CCNY group to provide clinicians and researchers with such a toolbox including reducing the burden automatic individual model creation, instant current calculation, and true montage optimization (eliminating the need for iterative search) are explained. Currently available software is summarized.